Profile of Enfortumab Vedotin in the Treatment of Urothelial Carcinoma: The Evidence to Date - Moussa M; Papatsoris A; Abou Chakra M; Dellis A (Dove Medical Press, 2021)
Mohamad Moussa,1 Athanasios Papatsoris,2 Mohamed Abou Chakra,1 Athanasios Dellis2,3 1Department of Urology, Al Zahraa Hospital, University Medical Center, Lebanese University, Beirut, Lebanon; 2 2nd Department of Urology, School of Medicine, Sismanoglio Hospital, National and Kapodistrian University of Athens, Athens, Greece; 3Department of Surgery, School of Medicine, Aretaieion Hospital, National and Kapodistrian University of Athens, Athens, GreeceCorrespondence: Athanasios Papatsoris 2nd Department of Urology, School of Medicine, Sismanoglio Hospital, National and Kapodistrian University of Athens, Athens, GreeceFax +302132058605Email agpapatsoris@yahoo.grAbstract: Nowadays the therapeutic landscape for advanced and metastatic urothelial carcinoma continues to evolve. The recent regulatory approval of enfortumab vedotin (EV) for the treatment of advanced urothelial cancer confirms the evolving role of antibody-drug conjugates. EV demonstrates a favorable profile in heavily pretreated patients with locally advanced or metastatic urothelial carcinoma. Early survival reports demonstrate a significant antitumor effectiveness along with a rather acceptable safety profile in a difficult-to-treat population.Keywords: enfortumab vedotin, bladder cancer, metastasis, urothelial cancer